(untitled) (Tempo e Argumento, 2023)
The purpose of the article is to address two central events in the trajectory of Alberto Besouchet. They are: his protagonism in the armed rebellion in Pernambuco in November 1935; and the episode of his disappearance while fighting alongside the republican troops against General Francisco Franco - during the Spanish civil war (1936-1939). For that end, this study will make use of the documentation of the Special Police Station for Political and Social Security (APERJ), sources of the Communist International (Edgard Leuenroth/Unicamp Archive), information notes by the leader of the Communist Party of Brazil (PCB) Honório de Freitas Guimarães (Documentation and Memory/Unesp), the newspaper A Classe Operária, as well as letters from brothers Augusto and Lídia Besouchet. On the condition that working with the character Alberto Besouchet allows the observance of the links between global and local antifascism, it is intended to analyze how he was inserted in the conflict between the different left molds in the interwar period.